Automorphisms of the Module Formal Sums - Dubrovin, Nikolay I. (Sarajevo Journal of Mathematics, 2019)
Besides Tychonoff topology on a direct product of discreet skew fields a variety of other topologies are defined and studied which correspond to given filters on the support. The main result of this paper is the description of continuous linear operators of a space of the formal sums.